Nuevo hallazgo de Nardophyllum genistoides (Phil.) Gray (Asteraceae) en Chile central - Muñoz-Schick, Mélica; Morales, Vanezza; Cruzat, María Eugenia; Moreira-Muñoz, Andrés (Gayana Botánica, 2010)
Nardophyllum genistoides (Phil.) Gray is recollected after a century and a half, in the same Region Metropolitana, Chile, at a new locality south of the original site. It grows around 1.600 masl, in the Río Clarillo National Reserve, associated to the sclerophyllous forest. The species is very rare, because only one plant was found.